“Prevalence of hypertension and cardiovascular risk factors in adolescents in the city of Guayaquil” P.C.R.F. - Aguirre Palacios, Fernando Antonio (Revista Universidad de Guayaquil, 2012)
Is a prospective, observational study in young people aged 11 to 13 years of age, to know the prevalence of HTA y 2 schools of Guayaquil randomly selected. 623 students were examined. Anthropometric data, Blood pressure and micro albuminuria test were taken. 54% were male and the BMI was 19.96 + 0.157 kg. Underweight was found in 3.8%, normal weight in 63.7%, overweight in 17.6%, and obesity in 14.7%. SBP averaged 109 ± 11mmhg, DBP was 60 ± 9mmhg, and MAP was 77 ± 7mmhg. Participants were classified as Pre hypertension with values of 121-129 mmhg, White coat hypertension with values of 130-139 and normalization of the values in two subsequent measurements, and HTA I with values of 140 mmhg. We found Pre HTA in 9,3% white coat in 3.2% and HTA I in 0.80%. There was no correlation between micro albuminuria and BP. Of the 6.74% with microalbuminuria, 47.6% were obese, 23.8% were overweight, and 28.5% had normal weight. The micro albuminuria test was of no relevance in kids with HTA, but could be influenced by obesity or Metabolic Syndrome. There is a relationship between cardiovascular history and the presence of HTA in youth, in contrast to the use of energy drinks, which showed no association.
Keywords: Hypertension; Microalbuminuria; Obesity